Evaluation of the Determinants of Cost Overrun in Real Estate Construction Projects in Awka, Anambra State - Muojama, L. C.; Ugonabo, C. U. (International Journal of Real Estate, 2025)
The evaluation of cost overrun determinants were carried out in this research study using descriptive statistical design tool to analyze survey reports from both professionals in the construction industry and investors/risk bearers. The investigative study involved 506 respondents comprising of Architects, Builders, Estate surveyors and Quantity surveyors in Awka Anambra state using a well-structured questionnaire design. Two research questions; what are the determinants of cost overrun in real estate construction projects in the study area? And, what are the effects and the level of effects of the determinants of cost overrun in real estate construction projects? And corresponding hypotheses guided the study. Descriptive statistics (mean, percentage and frequency) were adopted in answering the research questions, while regression analysis were used in angering the research hypotheses. Findings reveal that cost overrun occurs in real estate construction projects caused by various factors at different degrees ranging from project management factors to experience and service level factors, leading to abandoned projects, engagement of quacks, and indecision by the project owner. It was therefore recommended that real estate developers should adopt and implement advanced project planning tools and engaged certified project managers during real estate project construction, ensure effective communication and collaboration among the project stakeholders, hire experienced contractors, comply with the rules of regulatory bodies, and apply relevant construction technology in the project construction processes, among other suggestions.